2014
DOI: 10.4028/www.scientific.net/msf.802.415
|View full text |Cite
|
Sign up to set email alerts
|

Sintering Studies and Microstructural Evolution of Fe-MoS<sub>2</sub> Mixtures

Abstract: The development of dry self-lubricating materials is directly linked to the rising requirements of performance. Iron and steel are the most used metals around the world and molybdenum disulfide (MoS2) one of the most used solid lubricant. Therefore it is expected that one might try to develop self-lubricating steels containing MoS2, however MoS2 reacts with steel matrices during sintering. This work has focused on the study of these reactions; temperatures at which this occurs; the influence of particle sizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Graphite and MoS 2 with layered structure are more widely used solid lubricants (Jr et al , 2018), but it was found that graphite is easy to react with Fe to form diffuse hard spots (Dutkiewicz et al , 2015), which causes more damage to the mate parts. Furlan et al (2014) found that MoS 2 reacts with the iron matrix during sintering, which is completed at a temperature of 1050°C. For FeS and MoS 2 , graphite structure is similar, has good friction reduction properties and exhibits high chemical stability in the iron matrix at high temperatures; due to these characteristics as well as low cost, FeS can be introduced as a solid lubricant in iron-based self-lubricating materials (Peng et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Graphite and MoS 2 with layered structure are more widely used solid lubricants (Jr et al , 2018), but it was found that graphite is easy to react with Fe to form diffuse hard spots (Dutkiewicz et al , 2015), which causes more damage to the mate parts. Furlan et al (2014) found that MoS 2 reacts with the iron matrix during sintering, which is completed at a temperature of 1050°C. For FeS and MoS 2 , graphite structure is similar, has good friction reduction properties and exhibits high chemical stability in the iron matrix at high temperatures; due to these characteristics as well as low cost, FeS can be introduced as a solid lubricant in iron-based self-lubricating materials (Peng et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…MoS 2 is one of the most commonly used solid lubricants for Cu-Fe-based friction materials; it can be used to stabilize friction and improve the wear resistance of composites [6][7][8][9]. However, numerous studies have shown that MoS 2 reacts with Cu or Fe matrices when sintered at temperatures above 950°C [10][11][12][13][14][15][16][17][18][19][20][21]; our recent study revealed that the lubricity of MoS 2 is attributable to the resultant formation of metal sulfides such as FeS [21]. Because of its layered structure, good thermal stability, and low cost, FeS may be a suitable alternative to MoS 2 lubricants in the production of Cu-Fe-based friction materials.…”
Section: Introductionmentioning
confidence: 99%
“…the lubricant remains stable during the entire processing cycle. The compound MoS 2 , e.g., is widely used in combination with bronze matrices, but may react with iron matrices depending on the sintering temperature utilized (Miyoshi, 2001; Sustarsic et al, 2003; Dhanasekaran & Gnanamoorthy, 2007 a , 2007 b ; Furlan et al, 2012, 2014, 2015).…”
Section: Introductionmentioning
confidence: 99%